2016
DOI: 10.1088/1757-899x/136/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Soil-roots Strength Performance of Extensive Green Roof by Using Axonopus Compressus

Abstract: Abstract. Green roof technology has been proven to provide potential environmental benefits including improved building thermal performance, removal of air pollution and reduced storm water runoff. Installation of green roof also involved soil element usage as a plant growth medium which creates several interactions between both strands. This study was carried out to investigate the soil-roots strength performance of green roof at different construction period up to 4 months. Axonopus compressus (pearl grass) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Sambac and I. pes-caprae for thermal studies. Furthermore, Yusoff [8] used Axonopus Compressus and evaluated its soil-root strength performance. Therefore, these studies suggested that more species can be tested for their suitability as green roof vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Sambac and I. pes-caprae for thermal studies. Furthermore, Yusoff [8] used Axonopus Compressus and evaluated its soil-root strength performance. Therefore, these studies suggested that more species can be tested for their suitability as green roof vegetation.…”
Section: Introductionmentioning
confidence: 99%